Sustainability of Waqf Zurrī: Legal Analysis of Malaysia and Indonesia - Noor Lizza Mohamed Said; Mohamad Mu'az Fakhri Aziz; Mahmood Shaker Abood Alaloosh (Nusantara: Journal of Law Studies, 2026)
This study examines the sustainability of waqf zurrī through a statutory analysis of waqf zurrī legislation in Malaysia and Indonesia based on the views of classical jurists. Several Muslim-majority countries, such as Egypt, Tunisia, Libya, and the United Arab Emirates, have restricted and repealed waqf zurrī laws due to social, economic, and administrative factors, despite the absence of explicit Shariah prohibition. The main question is whether the legal frameworks in Malaysia and Indonesia contain sustainability elements capable of preventing the factors that led to the restriction and repeal of waqf zurrī in other Muslim countries. This study employs a qualitative doctrinal legal research design based on document analysis to evaluate sustainability elements within legal frameworks. The analysis focuses on Malaysian state waqf enactments, namely the Wakaf (Perak) Enactment 2015, the Wakaf (Terengganu) Enactment 2016, and the Wakaf (State of Selangor) Enactment 2015, as well as Indonesia’s Law of the Republic of Indonesia Number 41 of 2004 and Government Regulation of the Republic of Indonesia Number 42 of 2006, supported by fiqh analysis of juristic opinions. The findings indicate that sustainability elements within waqf zurrī legislation in Malaysia and Indonesia are reflected in statutory definitions, fundamental concepts of waqf zurrī, and governance mechanisms, including legal provisions, managerial competency, protection of family beneficiaries’ rights, continuity of benefits, protection of mawqūf from Improper Interference, and statutory authority for strengthening waqf zurrī. The study suggests that the statutory implementation of waqf zurrī in Malaysia and Indonesia can serve as a reference for other Muslim countries in ensuring the sustainability of waqf zurrī for the welfare of Muslim communities. This research contributes to contemporary fiqh discourse by discussing the sustainability elements reflected in waqf zurrī legislation in Malaysia and Indonesia based on the integration of Shariah principles and modern legal structures.